Reaction of common bean varieties to Fusarium spp. and Rhizoctonia solani in Mexican Highlands. - Navarrete-Maya, Rosa (2015)
Two trials were carried out at Texcoco, State of Mexico: in the first one 32 bean genotypes were sowed under irrigation on April 24 and May 8, 1997, in order to study their reaction to Fusarium spp. in a naturally infested soil. In the second one, protection against Fusarium spp. y R. solani was evaluated by applying captan or benomyl to the seeds of eight genotypes. In the first trial most genotypes were susceptible to Fusarium spp., particularly in the third evaluation (R6), on both sowing dates; with the exception of Negro Tacana and Amarillo de Calpan, both of which showed an intermediate reaction in the second sowing date. Incidence of Fusarium spp. was higher than 80%. On the first sowing date the Pinto Villa and Negro Perla genotypes were moderately resistant. In the second experiment the chemical treatment produced more vigorous seedlings. Pinto Villa and BAT 477 genotypes showed lower severity scores when treated with benomyl and captan, respectively. It was observed that plants of resistant genotypes survived because they developed adventitious roots.